Identification of key genes and immune infiltration of diabetic peripheral neuropathy in mice and humans based on bioinformatics analysis - Zhang, Yumin; Zhou, Hui; Liu, Juan; Zhou, Nan (Frontiers in Endocrinology, 2024)
Background: Diabetic peripheral neuropathy (DPN) is a common chronic complication of diabetes, while the underlying molecular mechanisms are still unclear. This study aimed to screen the key genes and the roles of immune infiltration in DPN using bioinformatics analysis. Methods: DPN mice datasets including GSE222778, GSE11343, GSE70852, GSE27382, and GSE34889 were retrieved from the GEO database. Data of human DPN were retrieved from the dbGaP. The differentially expressed genes (DEGs) were selected and further analyzed by using the Gene Ontology, Kyoto Encyclopedia of Genes and Genomes enrichment analysis, and Gene Set Enrichment analysis (GSEA) to find the shared key pathway. Protein-protein interaction networks were built in shared mice and human DEGs. The hub genes were selected and verified in vitro using high-glucose treated PC12 cells and Schwann cells. The single-sample GSEA (ssGSEA) algorithm was used to analyze the proportions of infiltrating immune cells in human DPN and the subsequent correlations with hub genes. Results: A total of 323 mice DEGs and 501 human DEGs were selected, and they were found significantly enriched in immune-related biological functions and pathways. Total 13 DEGs were found shared in mice and human DPN datasets, and among them there were 7 hub genes including PLAUR, S100A8, IL7R, CXCL13, SRPX2, CD300LB, and CFI. The expression of Cfi, S100a8, Cxcl13 and Cd300lb were consistently confirmed in vitro. The scores of Neutrophils and NK CD56bright cells varied most significantly by immune cell infiltration analysis (P<0.01). Besides the selected hub genes were found highly correlated with the immune infiltration. Conclusion: Our study indicated the importance of immune dysregulations in DPN and identified several hub genes through combined analysis in mice and human DPN samples, thus providing potential diagnostic and therapeutic targets in the future.